(3HgLI GdfGXQjf hCfS GdYGQajfs - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf eMeO GdRehQi,J (B977 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf PQjI fHjg eMeO Udi Gddg Ydjg hSde HJGL GdTQa hGdcQGeI s
(3BNQgG (B:s
(3BNQg eHJhQ jfJgi Hbhdg(B: (3EP HjJge HjJ NjQ hUdGM hhdGjI s
(3cde ajg eDdag Ydi QLGd GdCeZGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B239s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B707 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B69 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs